Predictive modeling of ascorbic acid degradation on simulated fruit juice and color changes in navel orange juice using response surface methodology - Diaz, Angelo R.; Gabriel, Alonzo A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
The study employed Response Surface Methodology (RSM) in establishing predictive models for the individual and interactive effects of different combinations of product and process parameters specifically, initial ascorbic acid (AA) content, pH, heating temperature, and heating time on the residual ascorbic acid (rAA) content and ascorbic acid percent change (%AAr) of simulated fruit juice (SFJ) systems. The effects of temperature, time, soluble solids (SS) and dilution rate on the Commission Internationale de l’Eclairage (CIE) color parameters on heated Navel orange juice were also characterized through predictive models using RSM. Central Composite Rotatable Design (CCRD) of experiment were used to generate the combinations needed to prepare the SFJs and Navel orange juice samples. Only the individual linear effects of temperature, time, and initial AA content significantly (P<0.05) influenced the rAA and %AAr while only the individual quadratic effects of temperature and initial AA content significantly influenced the %AAr in the heated SFJs. For the heated Navel orange juice, the linear effects of dilution significantly influenced all the CIE color parameters. Only the b* and Δb* values were significantly affected by the linear effects of SS. The interactive effects of SS and dilution significantly affected the L* and ΔL* values. Individual quadratic effects of temperature and time significantly influenced all CIE color parameters while only the L* and ΔL*, b* and Δb*, C* and ΔC*, and ΔE* were significantly influenced by the individual quadratic effects of SS and dilution rate. Validating systems for the rAA and %AAr predictive models were all within the acceptable accuracy range (1.00 – 1.60). On the other hand, validation of the models for CIE color parameters showed that 48 out of 80 (60%) systems were within the acceptable accuracy range. Results of the study may be used in designing heat process schedules for preservation and optimization of desired product quality.
Thesis (Bachelor of Science in Food Technology) -- University of the Philippines Diliman
Bibliography: pages 88-93.
Keywords: Citrus juices -- Philippines; Vitamin C -- Philippines